Plant maintenance system - Lee, Carmen Mun Yi (2010)
This report is divided into four sections, “Introduction”, “Project Plan”, “Proposed Solution”, and “Conclusion”. “Project Plan” and “Proposed Solution” form the main bulk of the report. The “Project Plan” gives a brief overview of the company background and its existing problems. This section also contains other information such as the scope, tasks and criteria of success, etc. of the project. The “Proposed Solution” section goes through the steps that the group have undergone in order to arrive at the proposed solution. This section includes three steps of analysis namely the problem, requirements and feasibility analysis, which will be followed by the logical design and physical design of the proposed system. Finally, this report will conclude with an evaluation of the group’s recommendations and a summary of how the information system can add value to KB Associates Pte Ltd.